Analysis of Tourism Potential and Marketing Integration in Mundeh Kangin Village - Sengkey, Fenny; Osin, Rosvita Flaviana (Akademi Komunitas MAPINDO, 2024)
The purpose of this research is to determine the tourism potential of Mundeh Kangin village, and howmarketing integration is carried out in Mundeh Kangin village, so that a suitable strategy can be implementedin the future. This research uses a qualitative descriptive approach with data collection techniques in the formof direct observation, interviews and document study. In-depth interviews with informants, namely the headof Mundeh Kangin Village, the tourism awareness group and the Farmer's group of Mundeh Kangin village. Thescope of the problem discussed in this research is regarding the potential and marketing mix of Mundeh KanginVillage as a pioneering tourism village in Tabanan Regency. Based on the results of internal, external andinteractive marketing research in Mundeh Kangin village, Tabanan, several key points can be concluded namelyLocal product potential, External communication challenges, and Role of Interactive marketing has beenidentified as a potential strategy to overcome challenges in external marketing. By involving the communitydirectly through social media, community events, interactive content, and collaboration with local influencers,interactive marketing is able to increase engagement and awareness about local products in Mundeh KanginTabanan village.Keywords: Tourism potential, integration, marketing